Epidemiology, outcomes and validation of RIFLE and AKIN criteria in acute kidney injury (AKI) in critically ill patients: Indian perspective. (July 2014) - Reddy, N. Pavan Kumar; K.P., Ravi; P., Dhanalakshmi; Annigeri, Rajeev; Ramakrishnan, Nagarajan; Venkataraman, Ramesh
Abstract Although the epidemiology and the impact of Acute Kidney Injury on outcomes are well-known in the Western literature, good data is lacking from India. Most studies published from India have not evaluated epidemiology of Acute Kidney Injury in the Intensive Care Unit setting and/or have not used validated criteria. In our observational study of 250 patients, admitted to a tertiary level ICU, we have explored the epidemiology of Acute Kidney Injury using both RIFLE and AKIN criteria and have validated them. We have also demonstrated that the severity of AKI is an independent predictor of mortality in critically ill patients. Our results are very much comparable to other studies and we feel that this study will remain as an epidemiological reference point for Indian clinicians dealing with AKI.